Teaching Style and Administration on Student Motivation: A Study from Kathmandu Valley - Mishra , Anisha; Choudhary, Satyanarayan; Shiwakoti, Rabindra (International Journal of Atharva, 2025)
Student motivation is key to academic success. This study examines how teaching style and administrative support impact student motivation in Kathmandu Valley. By analyzing different educational institutions, the research captures diverse student perspectives. A quantitative, descriptive research design was used. A total of 203 students from +2, bachelors, and master's levels participated. Data were collected via structured surveys, and correlation analysis assessed the relationships between teaching style, administration, and student motivation. Findings show that 35.5% of students prefer a good departmental relationship, 31.0% value an engaging instructor, 13.3% favor clear course content, and 20.2% prioritize self-efficacy. The most influential motivational factor was career motivation (49.8%), followed by teacher-created environment (23.2%), grade motivation (14.3%), and academic advice (12.8%). Correlation analysis showed a significant positive relationship between teaching style and motivation (r = 0.429, p = 0.000) and between administration and motivation (r = 0.525, p = 0.000). Hypothesis testing confirmed both teaching style and administration significantly impact student motivation. Teaching style and administrative support play a crucial role in student motivation. Effective instructional engagement and supportive administration enhance learning motivation. Future research could explore qualitative insights for a deeper understanding of motivational drivers.